Accounting for financial stability: Lessons from the financial crisis and future challenges - Jannis Bischof; Christian Laux; Christian Leuz (Leibniz Institute for Financial Research SAFE, 2020)
This paper examines banks' disclosures and loss recognition in the financial crisis and identifies several core issues for the link between accounting and financial stability. Our analysis suggests that, going into the financial crisis, banks' disclosures about relevant risk exposures were relatively sparse. Such disclosures came later after major concerns about banks' exposures had arisen in markets. Similarly, the recognition of loan losses was relatively slow and delayed relative to prevailing market expectations. Among the possible explanations for this evidence, our analysis suggests that banks' reporting incentives played a key role, which has important implications for bank supervision and the new expected loss model for loan accounting. We also provide evidence that shielding regulatory capital from accounting losses through prudential filters can dampen banks' incentives for corrective actions. Overall, our analysis reveals several important challenges if accounting and financial reporting are to contribute to financial stability.
Keywords: G21; G22; G28; G32; G38; K22; M41; M42; M48; 330; Banks; Financial crisis; Financial stability; Disclosure; Loan loss accounting; Expected credit losses; Incurred loss model; Prudential filter; Fair valueaccounting